DIFFERENCES IN DISCIPLINE CHARACTER BETWEEN STATE AND PRIVATE JUNIOR HIGH SCHOOL STUDENTS: ANALYSIS OF FAMILY AND SCHOOL DISCIPLINE PRACTICES, AND SELF-CONCEPT - Athaya Nadiya Asyhar; Dwi Hastuti (Journal of Child, Family, and Consumer Studies, 2023)
Disciplinary practices are instilled through routine activities as an effort to build adolescent habits, educated to behave well, and respect others. Disciplinary character can be applied well as a result of the formation of an optimal self-concept that is able to have a positive influence on discipline. The purpose of this study is to analyze the influence of family and school discipline practices, as well as self-concept on the disciplinary character of junior high school students. This study used a cross-sectional study design and purposive sampling technique with a total of 150 respondents who were students from public junior high schools, private junior high schools, and private religious-based junior high schools living at home with parents/other family members. The results of this study found that family discipline practices were in the high category, school discipline practices and discipline character were in the medium category, while self-concept was in the low category. The result of the T-test shows that state school students have a better disciplinary character than private and religious-based school students. PLS analysis shows that family and school discipline practices have a direct effect on self-concept and no direct effect on discipline character. The results of path analysis show that there is a significant influence of family and school discipline practices through self-concept on the disciplinary character of junior high school students.